Impact of levetiracetam on direct oral anticoagulant level and outcomes among older Asian patients with atrial fibrillation - Huang, Yu-Ting; Chen, Tzu-Ling; Huang, Yun-Lin; Kuo, Ching-Hua; Peng, Yu-Fong; Tang, Sung-Chun; Jeng, Jiann-Shing; Huang, Chih-Feng; Lin, Shin-Yi; Lin, Fang-Ju (Frontiers in Pharmacology, 2025)
ObjectiveThis purpose of this study is to analyze the influence of levetiracetam (LEV) on direct oral anticoagulant (DOAC) exposure and its implications for clinical outcomes.MethodsThis investigation comprised a retrospective cohort study utilizing the integrated medical database and a prospective observational study conducted in a tertiary hospital. Patients aged >65 years with atrial fibrillation and undergoing DOAC therapy were included and were categorized as LEV users and non-users based on LEV exposure status. In retrospective cohort, clinical outcomes between LEV users and non-users were compared, included ischemic stroke or transient ischemic attack (IS/TIA), systemic thromboembolism (STE) and major bleeding. In prospective cohort, DOAC trough concentration was measured.ResultsThe retrospective study included 191 LEV users and 694 matched LEV non-users. The risk of IS/TIA and STE were not significantly different between two groups (hazard ratio [HR], 0.99 [0.51–1.91] and 0.94 [0.49–1.79], respectively). For major bleeding, a non-significant higher risk was observed in the LEV-user group in contrast to the LEV-non-user group (HR 2.65 [0.43, 16.33]). The prospective analysis included 19 LEV users and 76 matched LEV non-users. Low DOAC concentrations were observed in 5.3% of LEV-users and 14.5% of LEV non-users (P = 0.53). High DOAC concentration were observed in 10.5% of LEV-users and 11.8% LEV non-users (P = 0.57). The association between LEV therapy and low or high DOAC concentration was non-significant.ConclusionConcurrent use of LEV and DOAC did not significantly affect DOAC exposure or clinical outcomes. LEV may be a safe anti-seizure medication for patients receiving DOAC therapy.